(untitled) (Vietnam Journal of Community Medicine, 2026)
The aorta is the “largest artery”, responsible for transporting oxygen-rich blood from the left ventricle to the organs. The aorta can be affected by acute factors as well as chronic inherited and/or acquired conditions that increase pressure on the aortic wall. In this study, we examine the characteristics of patients under 60 years of age who were hospitalized and treated at the Vietnam National Heart Institute from August 2024 to August 2025. The results show that the main reason for hospitalization was chest pain and abdominal pain. The prevalence of abdominal aortic aneurysm, thoracic aortic aneurysm, and thoracic aortic dissection was 13.9%, 23.8%, and 62.3%, respectively. The rates of surgical treatment, endovascular intervention, and medical management were 39.6%, 18.8%, and 42.6%, respectively. The mortality rate in the study was 7.9%, primarily due to septic shock and multiple organ failure.